The Ratcatcher and Other Stories - Kelly, Miles; Compiled by Parker, Vic (New York Belinda Gallagher, 2012)
These stories are fiendishly frightening to thrill, chill and thoroughly entertain young readers.
Include Color Illustrations
Keywords: Children's stories, English -- Fairy tales